T1 Bladder Cancer: Comparison of the Prognostic Impact of Two Substaging Systems on Disease Recurrence and Progression and Suggestion of a Novel Nomogram - Asimakopoulos, Anastasios D.; Colalillo, Gaia; Telesca, Rossana; Mauriello, Alessandro; Miano, Roberto; Di Stasi, Savino Mauro; Germani, Stefano; Finazzi Agrò, Enrico; Petrozza, Vincenzo; Caruso, Gianluca; Carbone, Antonio; Pastore, Antonio Luigi; et al. (Frontiers in Surgery, 2021)
Background T1 substaging of bladder cancer (BCa) potentially impacts on disease progression. Aim of the study was to compare the prognostic accuracy of two substaging systems on recurrence and progression of pT1 BCa and to test a nomogram based on pT1 substaging for predicting recurrence-free survival (RFS) and progression-free survival (PFS). Methods The medical records of 204 patients affected by primary T1 BCa were retrospectively reviewed. Substaging was defined according to the depth of lamina propria invasion in T1a-c and according to the extension of the lamina propria invasion to T1-microinvasive (T1m) or T1-extensive (T1e). Uni and multivariable Cox regression model evaluated the independent variables correlated to recurrence/progression. The predictive accuracy of the two substaging systems was compared by the Harrell’s C indexes. Multivariate Cox regression models for the RFS and PFS was depicted by a nomogram. Results 5-years RFS was 47.5% with a significant difference between T1c and T1a (p=0.020) as well as between T1e and T1m (p<0.001). 5-years PFS was 75.9% with a significant difference between T1c and T1a (p=0.011) as well as between T1e and T1m (p<0.001). Model T1m-e showed a higher predictive power than T1a-c for predicting RFS and PFS. In both the univariate and multivariate model subcategory T1e, tumor diameter and location and number of tumors were confirmed as factors influencing the recurrence and progression after adjusting for the other variables.The nomogram incorporating T1m-e model, showed a satisfactory agreement between model predictions at 5 years and actual observations. Conclusions Substaging is significantly associated to RFS and PFS for patients affected by T1 BCa. Further prospective studies with adequate numerosity should validate our preliminary outcomes and demonstrate whether the currently adopted nomograms calculating the risk of disease recurrence and/or progression worth implementation with the T1 substaging.